PENGOPTIMALAN PERANAN KOMISI PEMILIHAN UMUM DALAM VERIFIKASI FAKTUAL PADA PENCALONAN KEPALA DAERAH - Eriton, Muhammad (Jurusan Ilmu Sosial dan Ilmu Politik Fakultas Hukum Universitas Jambi, 2018)
General Elections initially known only as elections to elect the DPR, DPD, DPRD, President and Vice President directly but on the development of the election of regional head and deputy head of region directly has become part of the general election. As regional election organizer (PILKADA), the electoral commission in the region is divided into the Provincial, Regency and City General Election Commission. the problems that often arise in PILKADA are in the verification stage of administrative requirements of candidates, especially the verification of education certificates, the General Election Commission (KPU) should be obliged to coordinate with related parties regarding administrative requirements as a precautionary measure of fraud, but in reality in the process of verifying the requirements of candidates for regional head and the deputy head of the region is still lacking where the definition of verification is the examination and matching of the truth of written evidence relating to the validity of the fulfillment of requirements but in practice this meaning is only meant to be a necessity if there is fraud report, not as a duty as a precautionary measure against fraud execution of election District head.